Diabetic ketoacidosis at the onset of Type 1 diabetes in young children Is it time to launch a tailored campaign for DKA prevention in children - Iovane, Brunella; Cangelosi, Antonina Marta; Bonaccini, Ilaria; Di Mauro, Dora; Scarabello, Chiara; Panigari, Arianna; Tiri, Alessandra; Mastrorilli, Carla; Fainardi, Valentina; Dodi, Icilio; Vanelli, Maurizio (Acta Biomedica Atenei Parmensis, 2018)
Aim: To analyze clinical characteristics associated with the occurrence of diabetic ketoacidosis (DKA) at the onset of type 1 diabetes (T1D) in children aged